Стратегії класифікації ненормативної лексики - Клепуц, Леся (Видавництво Національного університету "Львівська політехніка", 2009)
The article deals with terminological equivalents to the concept of “bad language” in Ukrainian and foreign linguistics, problem of unified classification and characteristic of lexico-semantic groups, which come into stylistically low lexis and grounding of the belonging of each group to the non-standard language system.
Keywords: bad language; slang; jargon; argot; vulgarisms; obscene lexis